INOVASI SISTEM PELAYANAN MELENGKAPI IDENTITAS ORANG TERLANTAR DAN PEREKAMAN DISABILITAS UNTUK LENGKAPI IDENTITAS (SIPINTAR PEDULI) DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA PEKANBARU - Amelia Eka Putri; Ahmad Fitra Yuza (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2025)
The Pekanbaru City Population and Civil Registration Office created service innovations in meeting the needs of vulnerable people to obtain population identity, namely, the Service System to Complete the Identity of Displaced People and the Recording of Disabilities to Complete Identity (SIPINTAR PEDULI). SIPINTAR PEDULI is applied as a solution to the obstacles experienced by vulnerable people in accessing public services due to not having a population identity. SIPINTAR PEDULI is an electronic-based population administration service system, with the aim of overcoming the gap in population administration so that it makes it easier for vulnerable people to obtain population identity. The purpose of this study is to find out the innovation of the Service System to Complete the Identity of Displaced People and the Recording of Disabilities to Complete Identity (SIPINTAR PEDULI) and to find out the supporting and inhibiting factors of the innovation of the Service System to Complete the Identity of the Displaced Person and the Recording of Disabilities to Complete Identity (SIPINTAR PEDULI). In this study, a descriptive research type is used with a qualitative research type. Data collection in this study is carried out by observation, interviews and documentation as well as data analysis which includes data collection, data reduction, data presentation and drawing conclusions or verification. The result of this research is that the innovation of the Service System to Complete the Identity of Displaced Persons and the Recording of Disabilities to Complete Identity (SIPINTAR PEDULI) can meet the needs of vulnerable communities and make it easier for vulnerable people to obtain population identity.